2013
DOI: 10.1063/1.4826265
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and design of triple-band high-impedance surface absorber with periodic diversified impedance

Abstract: In this paper, a triple-band planar absorber with high-impedance surface (HIS) is designed and fabricated. The absorber structure is composed of polyurethane foam sandwiched between a lossy sheet of frequency selective surfaces (FSS) and a perfect electric conductor. The lossy FSS possesses different resistances in a periodic composite unit as compared with typical HIS absorber. Losses in the FSS are introduced by printing the periodic composite square ring pattern on blank stickers using various resistive ink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 21 publications
0
21
0
1
Order By: Relevance
“…3(b), we show R L2,opt (= R L3,opt ) as a function of v and h. When the distance between the Tx and Rx loops becomes large, R L,opt may become too small to be realized. This can be handled with a multi-turn Rx loop or an additional feeding loop or matching circuit [8][9][10] depending on the system requirements. 4 shows the coupling coefficients k 21 , k 31 , and k 32 depending on the distances v and h based on the same system configuration as described in Fig.…”
Section: Single-input Multiple-output Systemmentioning
confidence: 99%
“…3(b), we show R L2,opt (= R L3,opt ) as a function of v and h. When the distance between the Tx and Rx loops becomes large, R L,opt may become too small to be realized. This can be handled with a multi-turn Rx loop or an additional feeding loop or matching circuit [8][9][10] depending on the system requirements. 4 shows the coupling coefficients k 21 , k 31 , and k 32 depending on the distances v and h based on the same system configuration as described in Fig.…”
Section: Single-input Multiple-output Systemmentioning
confidence: 99%
“…Holloway et al reported the reflection and transmission properties of metafilm [7], in which it is proposed that the transmission and reflection properties can be controlled by changing the electric and magnetic polarizability. HIS, which consists of an array of frequency selective surfaces (FSS) over grounded dielectric layer is a good candidate for designing narrowband or wideband absorbers by introducing loss either to dielectric layer [6] or FSS layer [8,9], respectively. The narrowband absorbers designed by exploiting the dielectric loss of HIS layer are referred to as perfect metamaterial absorbers [6].…”
Section: Introductionmentioning
confidence: 99%
“…์ด ๋ฐฉ๋ฒ•๋„ ์‚ฌ์šฉ๋œ ฮป/4 ๋‘๊ป˜์˜ ์ฃผํŒŒ์ˆ˜ ์˜์กด์„ฑ์œผ๋กœ ๋Œ€์—ญํญ ์— ์ œํ•œ์ด ๋”ฐ๋ฅธ๋‹ค. ์ด์˜ ๊ทน๋ณต์„ ์œ„ํ•ด, ์ˆœ์ˆ˜์ €ํ•ญ์„ฑ ๋ฉด ๊ตฌ์กฐ ์˜ ์ ์ ˆํ•œ ๊ฐœ์„ ์„ ํ†ตํ•ด ฮป/4 ๋‘๊ป˜์˜ ์ฃผํŒŒ์ˆ˜ ์˜์กด์„ฑ์„ ์ƒ ์‡„ํ•  ์ˆ˜ ์žˆ๋Š” ๋ฆฌ์•กํ„ด์Šค๋ฅผ ๋ถ€๊ฐ€ํ•จ์œผ๋กœ์จ ๊ด‘๋Œ€์—ญํ™” ํ•  ์ˆ˜ ์žˆ๋Š” ์—ฐ๊ตฌ๊ฐ€ ์ง„ํ–‰๋˜์—ˆ๋‹ค [3]๏ฝž [5] . ์ด๋ฅธ๋ฐ” reactive screen์€ ์‹ญ ์ž๋ชจ์–‘์˜ ๊ฐ„๋‹จํ•œ ๊ตฌ์กฐ๋กœ ๊ตฌํ˜„๋  ์ˆ˜ ์žˆ์œผ๋ฉฐ, ๋„“์€ ํก์ˆ˜์œจ ๋Œ€์—ญํญ์„ ๊ฐ€์งˆ ์ˆ˜ ์žˆ๋‹ค [6] .…”
unclassified